The doped Co on Rh/Ni@Ni–N–C that weakened the catalytic performance for ammonia borane hydrolysis - Zhang, Zi-Hao; Liu, Lin-Chang; Zhang, Chen-Xi; Zhu, Hong-Lin; Zheng, Yue-Qing (International journal of hydrogen energy, 2023)
Alloy catalyst has been widely studied and used for hydrolytic dehydrogenation of ammonia borane (NH3BH3, AB) with excellent catalytic performance due to the synergistic effect of bimetal. Herein, a series of Rh1-xCox/Ni@Ni–N–C catalysts were prepared by an impregnation reduction method. The optimized Rh0.75Co0.25/Ni@Ni–N–C catalyst exhibited good catalytic performance with turnover frequency of 223.08 molH2 molcat−1 min−1 at 303 K, but decreased the catalytic performance compared with Rh/Ni@Ni–N–C. According to the XPS and Raman analysis, the RhCo alloy nanoparticles could be loaded at the defect position of Ni@Ni–N–C, and the Co nanoparticles occupied the intercalation between Rh and the defective site of the carrier, which could weaken the catalytic activity of AB hydrolysis. Based on the above research, we proposed the catalytic mechanism of the activation of the RhCo–H species. This work provides a new strategy for designing alloy-supported nano-catalysts. •The introduction of Co nanoparticles are occupied the position between Rh and defective site of Ni@Ni–N–C.•The introduction of Co nanoparticles reduce the catalytic activity of Rh/Ni@Ni–N–C.•The optimized catalyst Rh0.75Co0.25/Ni@Ni–N–C exhibits outstanding activity on hydrolysis of AB.